Pengembangan Model Permainan Lempar bagi Anak Tunagrahita Ringan di Sekolah Dasar Luar Biasa C - Hidayat, Arif; Muslimin, Muslimin; Sukmawati, Noviria; Hardiyono, Bayu; Kesumawati, Selvi Atesya; Fikri, Aprizal; Pratiwi, Aisyah (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This study aims to develop a learning model through a throwing game model for mildly disabled children at Sekolah Dasar Luar Biasa C that is valid and practical. The development of a throwing game model for mildly disabled children at Sekolah Dasar Luar Biasa C was carried out using the stages of development research according to Sugiyono, namely potential problems, data collection, product design, design validation, design revision, small scale trials, revision of small scale trials, large scale trials. The criteria for the validity of manipulative basic physical activity were assessed by two experts consisting of one learning media expert and one small game expert. Based on the results of expert review by experts, it shows that the throwing game model developed gets an average CVR of 0.56 which is included in the valid category and is tested on research responders. The results of the trial test of throwing games for mild tunagrahita children in Sekolah Dasar Luar Biasa C small-scale test were in the "very high" category with an average value of 12.31. These results provide reinforcement for the questionnaire results where the questionnaire results provide good / feasible results and the categories of small-scale and large-scale assessments obtained are high to very high. Keywords: children with mild intellectual disability, games, throwing